Estudos de obtenção de ésteres sintéticos derivados do óleo de babaçu visando aplicação como combustível de aviação - Oliveira, Vanessa Fernandes de (2018)
Aviation fuels used in gas-turbine engine powered aircrafts are mainly obtained from the distillation of mineral oil. Jet fuels molecules present carbon chain length of C8 to C16 in the same range of fossil kerosene and have high calorific values and a great cold behavior. With the increase in the consumption of jet fuels, it became extremely important to develop alternative fuels capable of fulfilling aviation industry requirements. In this context, aviation alternative fuel originated from sustainable raw materials must meet a set of safety requirements and should exhibit similar physicochemical properties to mineral kerosene. In this study, the production of a short-chain esters enriched biofuel using molecular distillation of methyl esters obtained from babassu oil was evaluated at different temperatures (100°C, 120 °C, 140 °C, 160 °C, 180 °C e 200 °C). Operational conditions were assessed to obtain high mass yields and high esters content in the carbon chain length range of kerosene. A fuel with properties close to those of aviation biofuels was obtained at 140°C. At this temperature, more than 80% of the esters in the product composition were within the desired range and there was a mass recovery of 88.1%. In addition, the short-chain esters enriched biofuel was blended with fossil kerosene at different concentrations and its properties were analyzed in order to study the effects of the gradual addition of this light biofuel to commercial aviation kerosene. A mixture up to 6.0% g/g accomplished the limit values established by ASTM D1655-17a for density, lower heating value and freezing temperature. In addition, babassu fatty acids were esterified with different alcohols, such as methanol, ethanol, propanol, isopropanol, isobutanol, 3-methyl-1-butanol and 2-ethylhexanol. The esters produced were evaluated for their physical-chemical properties, with reductions of around 21 °C for pour point, cloud point and freezing temperature.